2008
DOI: 10.1152/ajpregu.00880.2007
|View full text |Cite
|
Sign up to set email alerts
|

Tea catechin ingestion combined with habitual exercise suppresses the aging-associated decline in physical performance in senescence-accelerated mice

Abstract: echins, which are abundant in green tea, possess a variety of biologic actions, and their clinical application has been extensively investigated. In this study, we examined the effects of tea catechins and regular exercise on the aging-associated decline in physical performance in senescence-accelerated prone mice (SAMP1) and agematched senescence-accelerated resistant mice (SAMR1). The endurance capacity of SAMR1 mice, measured as the running time to exhaustion, tended to increase over the 8-wk experimental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…One possibility could be due to the effect of catechins on promoting mitochondrial biogenesis and fatty acid ␤-oxidation in muscle tissue (Holloszy and Booth 1976;Murase et al 2008). Yet another possibility is that the ingestion of catechins may enhance endurance capacity via activation of pathways controlling mitochondrial biogenesis (Baar et al 2002;Lee et al 2006;Murase et al 2008Murase et al , 2009). These effects of catechins on promoting mitochondrial biogenesis may help to explain why the attenuated training efficiency in response to chronic vitamin C/E administration was not seen in studies employing catechins-or GTE-based supplements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility could be due to the effect of catechins on promoting mitochondrial biogenesis and fatty acid ␤-oxidation in muscle tissue (Holloszy and Booth 1976;Murase et al 2008). Yet another possibility is that the ingestion of catechins may enhance endurance capacity via activation of pathways controlling mitochondrial biogenesis (Baar et al 2002;Lee et al 2006;Murase et al 2008Murase et al , 2009). These effects of catechins on promoting mitochondrial biogenesis may help to explain why the attenuated training efficiency in response to chronic vitamin C/E administration was not seen in studies employing catechins-or GTE-based supplements.…”
Section: Discussionmentioning
confidence: 99%
“…The catechins have been classified based on the number of hydroxyl groups within their chemical structures, including epicatechin (EC), gallocatechin, epigallocatechin (EGC), catechin gallate, gallocatechin gallate, epicatechin gallate (ECG), and epigallocatechin gallate (EGCG) (Higdon and Frei 2003;Hodgson et al 2013). Although many studies report positive effects of GTE on attenuating oxidative stress (Murase et al 2008;Panza et al 2008;Haramizu et al 2011) and improving endurance capacity (Murase et al , 2006Richards et al 2010), not all studies agree (Eichenberger et al 2009(Eichenberger et al , 2010. Moreover, to date, there is still little known about whether endurance training combined with GTE ingestion would impair the gain in endurance capacity following training in a sedentary population.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, mice, and rats, catechin exerts its main effects by decreasing fatty acid synthesis and stimulating hepatic lipid catabolism, leading to reduced liver and abdominal fat (Matsui et al, 2005;Murase et al, 2008). Under hot conditions, such as those of the present experiment, the animal stores energy in the form of fat because fat deposition is a very effi cient process, which contributes less to heat production (Webster, 1981).…”
Section: Resultsmentioning
confidence: 84%
“…The latter has been shown to be the major contributor to energy expenditure and heat production among the visceral organs (van Milgen et al, 1998). Moreover, Murase et al (2008) observed that catechin consumption reduces liver weight in mice. It is possible, therefore, that in the present study, cocoa husks have enforced the effect of temperature on liver weight loss, as catechin, epicatechin, and their oligomers constitute the main polyphenols in cocoa (Lecumberri et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It prevents apoptosis process by altering expression of the anti-and proapoptotic genes [16]. Long-term ingestion of tea decreases the age-related declines in physical performance and energy metabolism in senescence-accelerated mice [17]. Therefore, the aim of this study was to explore age-related changes in the jejunal mucosa of male Wistar albino rats and the possible protective role of GT administration.…”
mentioning
confidence: 99%